INFLUENCE OF DIGITAL TRANSFORMATION ON BANK COMPETITION - Сидская, Ольга (Socio-economic relations in the digital society, 2020)
Nowadays digital transformation of the banking sector is an inseparable part of the development of digital economy. The key IT-technologies transforming the modern banking system are studied in the article. The characteristic is given to Technologies that have recently been actively developed in banks are also characterized. The digitalization trends of the banking sector in the Republic of Belarus are considered in the article. At the moment the efficiency and competitiveness of banks largely depends on the introduction of the latest banking products and technological processes. In the study the opportunities that financial technologies afford to the digital economy are highlighted. The digital transformation of the banking sector provides numerous benefits for consumers of financial services, increases the quality, speed, accessibility of services and significantly improves the interaction between the consumers of financial services and financial organizations. At the same time, certain risks should be taken into account. That is why today we need integrated solutions that provide not only a high level of digitalization of banking business processes, but also reliable protection. That is why nowadays we need integrated solutions that provide not only a high level of digitalization of banking business processes, but also reliable protection. The author of the article analyzes the risks and benefits that digital transformation brings to banks. It is noted that all over the world banks actively close their branches and invest funds in mobile applications. The decrease in the number of banks both in developed and developing countries due to the development of technological innovations in the financial system is shown. The future of banks will depend on the options that they can offer in rapidly changing conditions. Several models of bank development in connection with the digital transformation are presented in the paper. Banks have to accelerate changing of existing business models in order to successfully integrate into the information society and digital economy. The results may be used to form the bank of the future.